Comparison between the Valsalva maneuver and intraoperative traction measurements in pelvic organ prolapse assessment. Issue 3 (27th September 2017) - Doumouchtsis, Stergios K.; Gauthaman, Nivedita; Khunda, Azar; Basu, Maya; Dadhwal, Kiran; Gayle, Yasmin V.; Durnea, Constantin M.
Abstract: Objective: To compare the assessment of pelvic organ prolapse (POP) between the Pelvic Organ Prolapse Quantification (POP‐Q) system with Valsalva maneuver and intraoperative measurement with mechanical traction. Methods: A prospective observational study included 100 women with POP attending a tertiary urogynecology clinic in the UK and undergoing vaginal prolapse surgical procedures between October 2011 and October 2014. The women were examined in the clinic using POP‐Q with the Valsalva maneuver and in the operating theater under general anesthesia with mechanical traction. The two sets of measurements were compared. Results: All POP‐Q measurements obtained with traction demonstrated significantly higher descent as compared with those measured by Valsalva maneuver (mean differences: Aa 0.64 cm; Ap 1.32 cm; Ba 0.96 cm; Bp 1.34 cm; C 3.57 cm; D 3.40 cm; all P <0.001). The perineal body and total vaginal lengths did not differ significantly. Conclusion: Measurements of six POP‐Q points obtained with traction showed a higher grade of POP than those assessed with Valsalva maneuver. On this basis, surgeons might decide on the extent of surgical procedure after examination under anesthesia; however, preoperative patient counselling would be essential to obtain consent for this approach. The clinical significance of the findings requires further evaluation. Abstract : For all POP‐Q points, a higher degree of pelvic organ prolapse was diagnosed intraoperatively with mechanical traction than preoperatively with the Valsalva maneuver.